Analisis peran mahasiswa dalam pembangunan pemberdayaan gampong Lam Gapang kecamatan Krueng Barona Jaya Kabupaten Aceh Besar - Teuku Naufal Mufid; Dr. Effendi Hasan, M.A.; Muliawati, S.IP., M.IP (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2021)
ABSTRACT, The role of student service towards the surrounding environment or the village that is occupied is an influence on the empowerment development of the surrounding community. With the presence of outstanding students, the expectations of the Lam Gapang community can have a good impact on community development and empowerment, but the facts that have occurred in Lam Gapang are very contrary to these expectations. The principle of Tri Dharma Universitas also comes from Pancasila so it is very unfortunate if he understands the aims and objectives of Pancasila and Tri Dharma of the University but cannot be implemented properly. The purpose of this study was to determine the causes of the lack of involvement of Unsyiah students in the empowerment development of Gampong Lam Gapang and solutions for the involvement of Unsyiah students in the empowerment development of Gampong Lam Gapang. The theory used is the Penta Helix Development Concept and Robert Chambers Village Empowerment Theory. Type of qualitative research. The data collection techniques used were interviews, observation and documentation. The results showed that the cause of the lack of involvement in the Empowerment Development of Gampong Lam Gapang lies in the dedication of students as academics who have gained more knowledge than the community, besides that students do not have access to support which causes miss communication between students and village officials. The solution to the problems that occur is to build good communication between students both with the community and with village officials, while students also need space to be able to participate in order to provide education about the empowerment development of Gampong Lam Gapang. The conclusion is that the role of students in the empowerment development of the Lam Gapang village has not been seen. This is evidenced by the lack of student dedication, accessibility, miscommunication and community participation. The solution so that students can be involved in empowerment development is to establish good communication between students and village officials, providing space for students to participate and educating the community about the programs to be run. Keywords: Role, Student, Development